1998
DOI: 10.1080/02841859809172178
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of doppler ultrasound in follow-up studies

Abstract: The short-term and long-term reliability of Doppler US was poor when the measurements were performed by a heterogeneous group of radiologists. The RI and PI measurements were somewhat more reliable than the PSV measurements and are recommended for use in follow-up studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Improvements of diagnostic tools such as duplex ultrasound, magnetic resonance tomography angiography, and multislice computed tomography angiography have lead to a more frequent diagnosis of renal artery stenosis during the last decade. [29][30][31][32][33][34][35][36][37][38][39][40][41] The cheapest and easiest to handle diagnostic tool is color duplex ultrasound. However, the accuracy of this method depends on the skill of the physician and the quality of the duplex machine 33 and is furthermore limited by not uniformly defined criteria for the detection of a hemodynamically relevant renal artery stenosis, e.g., a diameter stenosis of at least 70%.…”
Section: Diagnosis Of Renal Artery Stenosismentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements of diagnostic tools such as duplex ultrasound, magnetic resonance tomography angiography, and multislice computed tomography angiography have lead to a more frequent diagnosis of renal artery stenosis during the last decade. [29][30][31][32][33][34][35][36][37][38][39][40][41] The cheapest and easiest to handle diagnostic tool is color duplex ultrasound. However, the accuracy of this method depends on the skill of the physician and the quality of the duplex machine 33 and is furthermore limited by not uniformly defined criteria for the detection of a hemodynamically relevant renal artery stenosis, e.g., a diameter stenosis of at least 70%.…”
Section: Diagnosis Of Renal Artery Stenosismentioning
confidence: 99%
“…However, the accuracy of this method depends on the skill of the physician and the quality of the duplex machine 33 and is furthermore limited by not uniformly defined criteria for the detection of a hemodynamically relevant renal artery stenosis, e.g., a diameter stenosis of at least 70%. [32][33][34][35][36][37][38][39][40][41] The most specific parameter to detect a renal artery stenosis of at least 70% is a side difference of the intrarenal resistance index according to Pourcelot of at least 0.05 with a specificity of up to 100%. 32,35,39 It has been shown that serial duplex ultrasound examination during follow-up after primarily successful stent angioplasty of renal artery stenosis is able to detect restenosis with a high accuracy.…”
Section: Diagnosis Of Renal Artery Stenosismentioning
confidence: 99%
“…False-positive findings at transcranial Doppler US can be a result from poor reliability of velocity measurements and influence of many biologic factors on flow velocities (6)(7)(8)(9)(10). Standardization of transcranial Doppler US procedures among centers is problematic because efforts to reproduce recommended velocity values have shown differences (2,11,12).…”
mentioning
confidence: 99%
“…Without use of any contrast enhancement, US may be able to act as an alternative to contrast-enhanced MRI (36)(37)(38). Unlike MRI though, US is highly operator dependent and to perform some of the more specialist examinations well (renal Doppler, carotid Doppler), requires specialized training (39)(40)(41). Furthermore, attenuation of the US wave with distance from the probe can make it impossible to gain Doppler information from tissues that lie deep within the body.…”
Section: Alternatives To Mrimentioning
confidence: 99%